An Appraisal on the Value of Using Nutraceutical Based Senolytics and Senostatics in Aging - Kaur, Amanpreet; Macip, Salvador; Stover, Cordula M. (Frontiers in Cell and Developmental Biology, 2020)
The average human life expectancy has increased globally, and continues to rise, owing to the substantive progress made in healthcare, medicine, sanitation, housing and education. This ultimately enriches society with a greater proportion of elderly people. Sustaining a healthy aged population is key to diminish the societal and economic impact of age-related infirmities. This is especially challenging because tissue function, and thus wellbeing, naturally progressively decline as humans age. With age increasing the risk of developing diseases, one of the therapeutic options is to interfere with the molecular and cellular pathways involved in age-related tissue dysfunction, which is in part caused by the accumulation of senescent cells. One strategy to prevent this could be using drugs that selectively kill these cells (senolytics). In parallel, some compounds have been identified that prevent or slow down the progression of senescence or some of its features (senostatics). Senolytic and senostatic therapies have been shown to be efficient in vivo, but they also have unwanted dose-dependent side effects, including toxicity. Important advances might be made using bioactive compounds from plants and foods (nutraceuticals) if, as is proposed, they offer similar effectiveness with fewer side effects. The focus of this review is on the use of nutraceuticals in interfering with cellular senescence.